Perforated duodenal diverticulum - Olascuaga, Carlos; Borgno, Laura; González, Fernando (Cirugía del Uruguay, 1998)
The authors present a clinica/ case and make a bibliographical review of the international literature. Duodenal diverticu/a are relative/y frequent, they are the second nosological entity in the duodenum, after ulcerous disease, and duodenum is the second more frequent topography of diverticula of digestive tube. They are asymptomatic, except for complications which appear in a low percentage.